Meta-art: art of the 3-D user-created virtual worlds - Tasa, Umut Burcu; Gorgulu, Tulin (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2010)
User-created content and social networking have proved to be the most fundamental elements that shape how and why people use the Internet today. One concept that stems from and combines these two motives is 'metaverse', 3-D user-created virtual worlds. During the last few years, we have witnessed the rise of several metaverse attempts, and a growing art community within them, due to the possibilities they offer for building creative content. This paper develops from the historical evolution of metaverse, and the dynamic and transformative relationship between art and information and communication technologies (ICT), which has so far transformed the spectator into participator, user, and even creator of both the artwork and content in the web. It discusses and further proposes a form of 'meta-art', the native art form of a future metaverse, which inherits this transformative interplay between art and ICT and already existing art expressions in the current metaversal worlds.
Keywords: metaverse; user-created content; virtual worlds; art; collaboration; openness; interconnectedness; temporality